Effects of applying preslaughter feed withdrawal at the abattoir on behaviour, blood parameters and meat quality in pigs - Dalla Costa, F. A. [UNESP]; Devillers, N.; Paranhos da Costa, M. J. R. [UNESP]; Faucitano, L. (Elsevier B.V., 2016)
To study the effects of starting time of feed withdrawal on behaviour during loading and lairage, and meat quality (pH, colour and drip loss) in pigs, a total of 700 pigs were distributed into two groups. One group (FARM) was fasted for 18 hat the farm before transport and for 6 h before slaughter (including 2 h transport and 4 h lairage), while for the other group (PLANT) fasting time started at the departure from the farm (2 h transport plus 22 h lairage). Total fasting time was 24 h before slaughter for both groups. Fasting treatments did not influence blood parameters. PLANT pigs had longer fights (P < 0.05) than FARM pigs during lairage and produced darker (P = 0.02) and drier (P = 0.03) loins. Based on the results of this study, it may be preferable to commence feed withdrawal at the farm. Crown Copyright (C) 2016 Published by Elsevier Ltd. All rights reserved.
Keywords: Behaviour; Fasting; Lairage time; Meat quality; Pigs; Stress